UNJUST ENRICHMENT - Gunawan Widjaja; Mika Anabelle; Christina Herawati G; Grace Riana; Jessica Francis Gunawan (Cross-border, 2018)
The advantages and disadvantages in unjust enrichment itself are defined as a reciprocal system, in the sense that if on the one hand there is a loss, then on the other hand there will be an advantage. Unlike the concept of loss and gain in contractual relationships or unlawful acts, the criteria for profit and loss in unjust enrichment are more than just a value that can be calculated mathematically.